Kontestasi dan Kontekstualisasi Filsafat Islam di Tengah Modernitas - Fiqron, Mohamad Za'in (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Modernity is characterized by the growth and development of science and knowledge since the Renaissance movement occurred. As is known, there is a strong impression that Islamic philosophy has stopped after Ibn Rushd. There are even claims that Islamic philosophy has suffered a setback. This article aims to explain the contextualization of Islamic philosophy in the modern world and answer the challenges of modernity. This article includes qualitative research with a library model. The data is taken from various literature on Islamic philosophy, especially the latest references. Then it was analyzed using Heidegger's facticity hermeneutic method. Application in this study, the author tends to focus on the tendency of readers of various texts related to the topic of this article. The results of this study show that Islamic philosophy is able to respond to the splendor of modernity, namely the presence of a dialogue between tradition and modernity. In this way, intellectual heritage is not defeated by the development of modernity, but is contextualized by way of reconstruction or deconstruction. This reading is interesting because Islamic philosophy should receive special attention in the midst of the onslaught of science and secularization. So that the reading of Islamic philosophy is not obsolete, but needs further contextualization.